An existence and uniqueness theorem for the Navier–Stokes equations in dimension four. Issue 3 (17th February 2018) - Coscia, Vincenzo
Abstract: We prove that the steady state Navier–Stokes equations have a solution in an exterior Lipschitz domain of, vanishing at infinity, provided the boundary datum belongs to .